Depression and anxiety in adults with sickle cell disease: the PiSCES project - Levenson, James L; McClish, Donna K; Dahman, Bassam A; Bovbjerg, Viktor E; de A Citero, Vanessa; Penberthy, Lynne T; Aisiku, Imoigele P; Roberts, John D; Roseff, Susan D; Smith, Wally R (Psychosomatic medicine, 2008)
Depression and anxiety are common in sickle cell disease (SCD) but relatively little is known about their impact on SCD adults. This study measured prevalence of depression and anxiety in SCD adults, and their effects on crisis and noncrisis pain, quality-of-life, opioid usage, and healthcare utilization. The Pain in Sickle Cell Epidemiology Study is a prospective cohort study in 308 SCD adults. Baseline variables included demographics, genotype, laboratory data, health-related quality-of-life, depression, and anxiety. Subjects completed daily diaries for up to 6 months, reporting sickle cell pain intensity, distress, interference, whether they were in a sickle cell crisis, as well as health care and opioid utilization. Two hundred thirty-two subjects who completed at least 1 month of diaries were studied; 27.6% were depressed and 6.5% had any anxiety disorder. Depressed subjects had pain on significantly more days than nondepressed subjects (mean pain days 71.1% versus 49.6%, p < .001). When in pain on noncrisis days, depressed subjects had higher mean pain, distress from pain, and interference from pain. Both depressed and anxious subjects had poorer functioning on all eight SF-36 subscales, even after controlling for demographics, hemoglobin type, and pain. The anxious subjects had more pain, distress from pain, and interference from pain, both on noncrisis pain days and on crisis days, and used opioids more often. Depression and anxiety predicted more daily pain and poorer physical and mental quality-of-life in adults with SCD, and accounted for more of the variance in all domains of quality-of-life than hemoglobin type.